The Making of a Continental Financial System : Lessons for Europe from Early American History - Gaspar, Vitor (IMF Working Papers; Working Paper ;, 2014)
Alexander Hamilton was the first U.S. Treasury Secretary from 1789 to 1795. When he started, the Federal Government was in default. During his tenure, U.S. Treasuries became the ultimate safe asset. He successfully managed expectations, achieved debt service reduction, and stabilized financial panics. He delivered sound public finances and financial stability. In the end, the U.S. possessed a modern financial system able to finance innovation and growth. At a time when Europe is working its way out of the sovereign debt crisis and implementing Banking Union and Financial Union, it is worthwhile to search for lessons from early U.S. history.